Influence of the Cultural Background at Small and Medium Sized-Enterprises Innovations in Regional Dimension - Maria Bernat; Anna Bruska; Anna Jasinska- Biliczak (Institute of Economic Research (IER), 2017)
SME's play crucial role in economy's development. In EU they make up 99% of all enterprises and are at the forefront of technological innovations (Kotler et al., 1999, pp. 139-140; EC 2013, p. 2; Jasinska-Biliczak, 2016, p. 30). Being the flywheel for economies (Soininen et. al., 2012, p. 614) are called 'hidden champions' of 20th century. Over past few years Europe-wide analyses (Griffin, 2004, p. 424) have emphasised the importance of investing in SME's. Taking into consideration that cultural environment is the background to decisions: social, managerial, development (Hofstede et al., 2011, p. 46), so innovations, knowledge, skills and competences as well as culture reinforce each other. Research is the attempt of pointing the cultural background role in the SME's innovations and in the regional economy at the example of Opole Region. Results will contribute to stimulate, develop and adopt the policies at regional level, which aim regional dimension of SME's growth and their cultural base. Methods of desk research were applied with fields research using in-depth interviews to achieve research purpose. Mapping as the interdisciplinary visualization technology permitted to clarify research results. The phenomenon of cultural background for innovations in SME's was studied in regional dimension. Research allows to state that in analysed region, strongly settled in multicultural environment, cultural background turns out to be factor influencing innovations in SME's. So regional authorities should take that finding into account when planning regional policy, especially focused on enterprises' development. The use of cultural factor as strong side of the enterprise should be promoted as well as experiences based at the cultural backgrounds exchanged between SME's in region. So integrated action plans may enhance the best practise spreading in region and contribute innovative growth in SME's sector.
Keywords: O31; O47; R11; 330; innovations in small and medium enterprises; SME's growth; innovation; cultural background; SME's regional dimension